2016
DOI: 10.1108/hff-01-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal damage of tissues embedded with large blood vessels during plasmonic photo-thermal heating (PPTH)

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Simulations [41] have shown that using gold nanoparticles for photothermal treatments enables the containment of the temperature to a much narrower field than using laser irradiation only, also in the presence of large blood vessels that act as heat sinks. [42] This could be confirmed during in vivo photothermal experiments [43] where the enhanced optical extinction confined the source of the resultant heat to nanoparticle-containing tissue. This resulted in a steep temperature gradient at the tumor boundary that confines thermal damage to the target tissue.…”
Section: Particle-based Controlled Heatingmentioning
confidence: 82%
“…Simulations [41] have shown that using gold nanoparticles for photothermal treatments enables the containment of the temperature to a much narrower field than using laser irradiation only, also in the presence of large blood vessels that act as heat sinks. [42] This could be confirmed during in vivo photothermal experiments [43] where the enhanced optical extinction confined the source of the resultant heat to nanoparticle-containing tissue. This resulted in a steep temperature gradient at the tumor boundary that confines thermal damage to the target tissue.…”
Section: Particle-based Controlled Heatingmentioning
confidence: 82%
“…We assessed the impact of a blood vessel on LITT outcomes, assuming the vessel acts as a heat sink. Prior investigations, such as the work by Verhey et al and Paul et al have shown that the presence of large vessels may result in asymmetric temperature and thermal damage results in response to LITT [9,11,12,20]. In building on this work, we examined the impact of the vessel on a clinically relevant treatment planning scenario.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…This is in line with the notion that vessels under a certain size, which have a smaller capacity to carry away heat, end up being completely occluded during treatment. Several investigators built on this work by developing their own models that consider more complex flow patterns and cases with multiple vessels [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PDT/PTT synergistic therapy can improve the therapeutic efficacy and may provide a promising strategy for ablating the complicated and metastatic malignancies while minimizing side effects. [137][138][139] Gan et al developed indocyanine green@covalent organic framework-1@polydopamine (ICG@COF-1@PDA) nanosheets as phototherapeutic agents for PDT/PTT dual-modal tumour therapy. 98 ICG@COF-1@PDA improved tumour elimination to release abundant endogenous tumour neoantigens, thus triggering effective anti-tumour immune responses (Fig.…”
Section: Chem Soc Rev Tutorial Reviewmentioning
confidence: 99%